Mapping Soil Fertility Status of Alluvial Formations Using the SFI Method and Kriging Interpolation Geographic Information Systems - Basuki Basuki; Aisyah Fatmawati; Fahmi Arief Rohman (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Land degradation can be characterized by a decrease in soil productivity. Jember Regency has the potential to develop food crop commodities. A decrease in soil productivity can be caused by a decrease in soil fertility. The study aims to look at the index and distribution of soil fertility in rice fields in southern Jember. The SFI (soil fertility index) technique was utilized in this study to calculate the soil fertility index. SFI is broken down into multiple parts, including calculating the Minimum Soil Fertility Index (MSFI), weighting, and scoring, which are then incorporated into the SFI calculation. The determination of MSFI is done using principal component analysis (PCA). The results of the MSFI analysis involved spatial mapping using kringing analysis to determine the area distribution of each class. The soil fertility index of the research location ranged from 1.72 to 2.28, with a low-class area of 9,224.19 ha (99.522%) and a very low-class area of 44,266 ha (0.478%). Parameters that influence soil fertility levels include cation exchange capacity, total soil nitrogen, and soil organic carbon, with a cumulative value of 84.8%. Keywords: Kriging interpolation, MSFI, paddy field, soil fertility index, soil mapping.